Humane Euthanasia Procedures for Sick, Injured, and/or Debilitated Livestock Wall Chart - Jan K. Shearer; Paul Nicoletti (EDIS, 2007)
VM-153, a full-color wall chart by Jan K. Shearer and Paul Nicoletti, describes the correct way to humanely euthanize cattle using gunshot or penetrating captive bolt. Published by the UF Department of Veterinary Medicine -- Large Animal Clinical Sciences, April 2007.